Analisis Rantai Pasok Kopra di Desa Tolombukan Satu Kecamatan Pasan Kabupaten Minahasa Tenggara (Analysis of Copra Supply Chain in Tolombukan SatuVillage Pasan Sub District South Minahasa Regency) - Josua Nolly Lumintang; Caroline B. D. Pakasi; Grace A. J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to to determine the supply chain of copra in Tolombukan Satu Village. This research was conducted from October to December 2021. The sampling technique in this study used a random sampling technique (simple random). The research results showed that the product flow that occurs in Tolombukan Satu Village has 2 distribution channels. The first channel has 4 stakeholders, namely farmers, collectors, suppliers, factories. The second channel has 3 stakeholders, namely farmers, suppliers, and factories. Collectors distribute copra to factories who queue up to 2 days, so it takes more time to distribute copra to factories. Financial flows flow from factories to farmers through suppliers who pay copra to collecting traders through direct transactions and transfers, collecting traders pay copra to farmers through direct transactions, there are also farmers who take cash before harvesting the coconuts. However, transfer transactions often result in late payments by suppliers. The flow of information is divided into two directions, from farmers to collectors, collectors to suppliers, and suppliers to factories, and vice versa which is done intensively.